Thyroid cancer incidence trend and association with obesity, physical activity in the United States - Biaoyou Chen; Zhaomin Xie; Xuwei Duan (BMC, 2022)
Abstract Background State-level racial/ethnic and age differences and the temporal trend of thyroid cancer (TC) incidence in the USA remain unknown. Our research purposes include: Characterizing state-level temporal variation in TC incidence; examining the disparities of TC incidence by state-level race/ethnicity and age; performing an ecological correlation between TC incidence and obesity/physical activity. Methods TC incidence data during 2000-2017 were extracted from the United States cancer statistics. Using joinpoint regression to evaluate TC incidence trends. Annual percent change (APC), average APC (AAPC) and incidence rates were calculated. The obesity prevalence and physical activity level at the state-level were extracted from Behavioral Risk Factor Surveillance System, and the association between state-level AAPC of TC and obesity/physical activity was tested by Pearson correlation coefficient. Results We found that the TC incidence had shown an overall downward trend in recent years, but 10 states continued increasing. There were significant differences in state-level race/ethnicity (non-Hispanic Whites as a reference) and age group (45-59 age group as a reference) incidence: Incidence Rate Ratio (IRR) was 0.4-1.2 for non-Hispanic Blacks, 0.7-1.6 for non-Hispanic Asian and Pacific Islanders, 0.4-1.2 for non-Hispanic American Indians/Alaskan Natives, and 0.5-1.3 for Hispanics. High IRR in young people were distributed in northern USA, while in older people were distributed in south. The state-level obesity/physical activity level and AAPC had a weak correlation (r = 0.34, P = 0.016) and inverse weak correlation (r = -0.29, P = 0.037), respectively. The AAPC of states with a consistent increasing trend had an extremely strong correlation with obesity prevalence (r = 0.80, p = 0.006), and an inverse strong correlation with physical activity level (r = -0.65, P = 0.04). Conclusions Thyroid cancer incidence in 10 states continued increasing. State-level variation in race/ethnicity and age group incidence were found. Lifestyle and environmental factors may interfere with the incidence trend of TC in the USA.